A Prospective, Multicenter, Single-Blind, Randomized, Controlled Study of VYC-15L, a Hyaluronic Acid Filler, in Adults for Correction of Infraorbital Hollowing. (5th August 2021) - Fabi, Sabrina; Zoumalan, Christopher; Fagien, Steve; Yoelin, Steve; Sartor, Marta; Chawla, Smita
Abstract: Background: Rejuvenation of the under-eye area is a popular facial aesthetic treatment option. Objectives: This study evaluated the safety and effectiveness of VYC-15L for the correction of moderate or severe infraorbital hollowing. Methods: This was a randomized, controlled, single-blind study with a primary endpoint defined as the proportion of participants with ≥1-grade improvement at Month 3 assessed by an evaluating investigator employing the Allergan Infraorbital Hollow Scale. Three-dimensional imaging was conducted to assess infraorbital volume up to Month 12. Procedure pain and injection-site responses (ISRs) were documented, and safety was monitored throughout the study. Results: At Month 3, the difference between treatment (83.1%) and control (15.6%) was 67.5% (95% CI = 52.9 to 82.0, P < 0.0001). 3D imaging showed a mean volume increase from baseline of 0.733 mL (left) and 0.777 mL (right) at Month 12. Mean pain scores were ≤1.7 (scale of 0 to 10). Most ISRs with initial treatment were mild/moderate and resolved in ≤1 week, including tenderness (49.5%), bruising (42.7%), and swelling (41.7%). Thirty-four participants had treatment-emergent adverse events (TEAEs), of which 14 (10.3%) had treatment-related TEAEs, including bruising (3.8%) and swelling/edema (2.9%), which resolved in ≤2 weeks. Three participants had swelling/edema starting >30 days posttreatment; 2 resolved in ≤4 days, 1 by 45 days. No treatment-related serious AEs were reported. Conclusions: VYC-15L was safe and effective for the correction of moderate or severe infraorbital hollowing and lasted through 1 year. Level of Evidence: 2: